1)5у-(13+у)=у+14 2)3(2х-4)-2(х+3)=-2 3)4у-3=2(7-у)+1

gerasi1 gerasi1    2   20.05.2019 21:10    0

Ответы
jjrey252 jjrey252  14.06.2020 11:21

5у-(13+у)=у+14 

5у-13-у=у+14

5у-у-у=14+13

3у=27

у=27:3

у=9

ответ:9

 

3(2х-4)-2(х+3)=-2

6х-12-2х-6=-2

6х-2х=-2+12+6

4х=16

х=16:4

х=4

ответ:4

 

 

4у-3=2(7-у)+1

4у-3=14-2у+1

4у+2у=14+1+3

6у=18

у=18:6 у=3

ответ:3

 

ПОКАЗАТЬ ОТВЕТЫ
Вичка03 Вичка03  14.06.2020 11:21

5у-(13+у)=у+14

5у-13-у=у+14

5у-у-у=14+13

3у=27

у=27;3

у=9

 

3(2х-4)-2(х+3)=-2

6х-12-2х-6=-2

6х-2х=-2+12+6

4х=16

х=16;4

х=4

 

4у-3=2(7-у)+1

4у-3=14-2у+1

4у+2у=14+1+3

6у=18

у=18;6

у=3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика